Effect of nanotechnology in self-etch bonding systems on the shear bond strength of stainless steel orthodontic brackets - Shaza M. Hammad; Noha El-Wassefy; Ahmed Maher; Shafik M. Fawakerji
ABSTRACT Objective: To evaluate the effect of silica dioxide (SiO2) nanofillers in different bonding systems on shear bond strength (SBS) and mode of failure of orthodontic brackets at two experimental times. Methods: Ninety-six intact premolars were divided into four groups: A) Conventional acid-etch and primer Transbond XT; B) Transbond Plus self-etch primer; and two self-etch bonding systems reinforced with silica dioxide nanofiller at different concentrations: C) Futurabond DC at 1%; D) Optibond All-in-One at 7%. Each group was allocated into two subgroups (n = 12) according to experimental time (12 and 24 hours). SBS test was performed using a universal testing machine. ARI scores were determined under a stereomicroscope. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to determine the size and distribution of nanofillers. One-way ANOVA was used to compare SBS followed by the post-hoc Tukey test. The chi-square test was used to evaluate ARI scores. Results: Mean SBS of Futurabond DC and Optibond All-in-One were significantly lower than conventional system, and there were no significant differences between means SBS obtained with all self-etch bonding systems used in the study. Lower ARI scores were found for Futurabond DC and Optibond All-in-One. There was no significant difference of SBS and ARI obtained at either time points for all bonding systems. Relative homogeneous distribution of the fillers was observed with the bonding systems. Conclusion: Two nanofilled systems revealed the lowest bond strengths, but still clinically acceptable and less adhesive was left on enamel. It is advisable not to load the brackets immediately to the maximum.